Contrasting Complement Control, Temporal Adjunct Control and Controlled Verbal Gerund Subjects in ASD: The Role of Contextual Cues in Reference Assignment - Janke, Vikki; Perovic, Alexandra (Frontiers in Psychology, 2017)
This study examines two complex syntactic dependencies (complement control and sentence-final temporal adjunct control) and one pragmatic dependency (controlled verbal gerund subjects) in children with ASD. Sixteen high-functioning (HFA) children (aged 6 to 16) with a diagnosis of autism and no language impairment, matched on age, gender and non-verbal MA to one TD control group, and on age, gender and verbal MA to another TD control group, undertook three picture-selection tasks. Task 1 measured their base-line interpretations of the empty categories (ec). Task 2 preceded these sentence sets with a weakly established topic cueing an alternative referent and Task 3 with a strongly established topic cueing an alternative referent. In complement control (Ron persuaded Hermione ec to kick the ball) and sentence-final temporal adjunct control (Harry tapped Luna while ec feeding the owl), the reference of the ec is argued to be related obligatorily to the object and subject respectively. In controlled verbal-gerund subjects (ec Rowing the boat clumsily made Luna seasick), the ec’s reference is resolved pragmatically. Referent choices across the three tasks were compared. TD children chose the object uniformly in complement control across all tasks but in adjunct control, preferences shifted towards the object in Task 3. In controlled verbal-gerund subjects, they exhibited a strong preference for an internal-referent interpretation in Task 1, which shifted in the direction of the cues in Tasks 2 and 3. HFA children gave a mixed performance. They patterned with their TD counterparts on complement control and controlled verbal-gerund subjects but performed marginally differently on adjunct control: no TD groups were influenced by the weakly established topic in Task 2 but all groups were influenced by the strongly established topic in Task 3. HFA children were less influenced than the TD children, resulting in their making fewer object choices overall but revealing parallel patterns of performance. In this first study of three sub-types of control in ASD, we demonstrate that HFA children consult the same pragmatic cues to the same degree as TD children, in spite of the diverse pragmatic deficits reported for this population.